2011
DOI: 10.4049/jimmunol.1003348
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 2 Is a Feedback Inhibitor of TLR-Induced Activation in Human Monocyte-Derived Dendritic Cells

Abstract: Dendritic cells (DCs) are key players in initiating and directing the immune response. Therefore, their activation state and functional differentiation need to be tightly controlled. The activating stimuli and their signaling networks have long been an area of focus in DC research. Recent investigations have also shed light on the mechanisms of counterregulation and fine-tuning of DC functions. One class of proteins involved in these processes is the family of suppressors of cytokine signaling (SOCS), whose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 52 publications
(54 reference statements)
8
60
0
1
Order By: Relevance
“…al also demonstrated that the silencing of SOCS2 results in enhanced cytokine production, especially in case of IL-10 and IL-1β [73]. Our results corroborate these findings as we detected enhanced relative gene expression of IL-10 after PGN stimulation ( Figure 10G).…”
Section: Socs Proteins Have Function In the Regulation Of Pgn Inducedsupporting
confidence: 82%
See 1 more Smart Citation
“…al also demonstrated that the silencing of SOCS2 results in enhanced cytokine production, especially in case of IL-10 and IL-1β [73]. Our results corroborate these findings as we detected enhanced relative gene expression of IL-10 after PGN stimulation ( Figure 10G).…”
Section: Socs Proteins Have Function In the Regulation Of Pgn Inducedsupporting
confidence: 82%
“…Moreover, in T+PGN samples we detected a more robust gene expression down regulation than in N+PGN samples. It is important to note here that Posselt and his colleagues demonstrated that in primary human monocytederived DCs, SOCS2 shows a time-delayed expression pattern after LPS stimulation [73].…”
Section: Socs Proteins Have Function In the Regulation Of Pgn Inducedmentioning
confidence: 99%
“…Upon induced inflammatory challenge, absence of SOCS2 has been shown to render multiple immune cell types incapable of mounting anti-inflammatory responses. Under resting conditions, SOCS2 null animals also display a population-bias towards a proinflammatory phenotype (Machado et al, 2006;Lee et al, 2010;Knosp et al, 2011;Posselt et al, 2011;Hu et al, 2012). SOCS2 is known to inhibit TGFβ, IL-4, IL-5, IL-10, IL-13 and IFNγ signaling (Knosp et al, 2011, Knosp et al, 2013.…”
Section: Inflammationmentioning
confidence: 99%
“…SOCS2 also accelerates degradation of other members of the SOCS family such as SOCS1 and SOCS3 thus further impinging on downstream STAT signaling (Piessevaux et al, 2006;Tannahill et al, 2005). In turn, SOCS2 gene itself is under regulation of various inflammatory signals (e.g., LPS, dioxins, LipoxinA4) (Machado et al, 2006;Hu et al, 2009bHu et al, , 2012 and cytokines (e.g.,IL-4, IL-10, IFNβ, IFNγ) (Knosp et al, 2011;Posselt et al, 2011).…”
Section: Inflammationmentioning
confidence: 99%
“…ограничивая провоспалительную активацию анти-генпрезентирующих клеток, а также натуральных киллеров (NK) [6][7][8][9]. Таким образом, состояние JAK/STAT-сигнального пути определяет эффективность про-цессов пролиферации, дифференцировки, роста, противовирусного ответа и т.д.…”
unclassified